Comparison of two different modes of molecular adsorbent recycling systems for liver dialysis - Soo, Euan; Sander, Anja; Heckert, Karlheinz; Vinke, Tobias; Schaefer, Franz; Schmitt, Claus P. (Pediatric nephrology, 2016)
In children acute liver failure is a rare but life-threatening condition from which two-thirds do not recover with supportive therapy. Treatment is limited by the availability of liver transplants. Molecular adsorbent recirculating system (MARS) dialysis is a bridge to transplantation that enhances the chances of survival during the waiting period for a transplant, although it cannot improve survival. Open albumin dialysis (OPAL) is a new mode of albumin dialysis developed to further improve dialysis efficiency.
Gesehen am 12.05.2020
Im Text wurde irrtümlich bei Autoren "Sanders" geschrieben